Representasi Kadar Methemoglobin (Methb) Akibat Paparan Pestisida pada Petani di Sigi Biromaru - Intania Riska Putrie; Tri Setyawati; Devi Oktafiani; Ryka Marina Walanda; Listawati; Putrie, Intania Riska (LPPM STIKES Guna Bangsa Yogyakarta, 2025)
Pesticides can be toxic and disrupt the ecosystem if used for long periods in high doses. High toxicity due to intensive pesticide exposure will affect heme biosynthesis. Oxygen is carried by red blood cells that contain Fe2+ ions bound to hemoglobin. Exposure to toxic pesticides will cause Fe2+ ions to oxidize to Fe3+, resulting in hemoglobin changing into Methemoglobin (MetHb). This causes Hb to be unable to bind with oxygen, resulting in anemia. Methemoglobin measurement is important for farmers because they are at high risk. This measurement can also be used for early detection, prevention of complications, and evaluation of pesticide exposure. This study aims to determine MetHb levels in farmers intensively exposed to pesticides. This study used a cross-sectional design with a stratified sampling technique. This study used 50 farmers who were directly exposed to pesticides. The sample used was a 3cc venous blood sample taken using a syringe. The blood sample was then measured for MetHemoglobin levels using a spectrophotometer. This research was conducted in two villages, namely Kalukubula Village and Lolu Village. In Kalukubula Village, the average MetHemoglobin level was 6.53%, with the lowest level being 2.95% and the highest level being 9.95%. In Lolu Village, the average MetHemoglobin level was 5.72%, with the lowest level being 1.80% and the highest level being 9.60%. Normal MetHemoglobin levels in humans range from 0-3%. MetHemoglobin levels in farmers in Sigi Biromaru mostly showed Asymptomatic Methemoglobin results, meaning that most farmers suffer from MetHemoglobin but do not show clinical symptoms.